Penerapan Arsitektur Kontemporer Pada Rumah Sakit Jiwa Tipe B Di Kota Tangerang - Annissa Yuniawati; Putri Suryandari; Anggraeni Dyah Sulistiowati (MAESTRO, 2022)
Mental Hospital is a place to fulfill the healing of mental disorders with a promotive, preventive, curative, and rehabilitative approach that is held thoroughly, integrated, and continuously and can restore a person's condition so that they can carry out daily activities and social activities normally again. With the design of the Mental Hospital building in the city of Tangerang, it is hoped that it can support to meet the needs in restoring one's mental condition. The concept of contemporary architecture applied to the façade of the building is expected to reduce the negative stigma and discrimination that families or patients get when visiting a mental hospital.